T2 Turbo Spin Echo With Compressed Sensing and Propeller Acquisition (Sampling k-Space by Utilizing Rotating Blades) for Fast and Motion Robust Prostate MRI: Comparison With Conventional Acquisition. Issue 3 (2nd March 2023) - Bischoff, Leon M.; Katemann, Christoph; Isaak, Alexander; Mesropyan, Narine; Wichtmann, Barbara; Kravchenko, Dmitrij; Endler, Christoph; Kuetting, Daniel; Pieper, Claus C.; Ellinger, Jörg; Weber, Oliver; Attenberger, Ulrike; et al.
Abstract : Objectives: The aim of this study was to compare a new compressed sensing (CS) method for T2-weighted propeller acquisitions (T2CS ) with conventional T2-weighted propeller sequences (T2conv ) in terms of achieving a higher image quality, while reducing the acquisition time. Materials and Methods: Male participants with a clinical suspicion of prostate cancer were prospectively enrolled and underwent prostate magnetic resonance imaging at 3 T. Axial and sagittal images of the T2conv sequence and the T2CS sequence were acquired. Sequences were qualitatively assessed by 2 blinded radiologists concerning artifacts, image-sharpness, lesion conspicuity, capsule delineation, and overall image quality using 5-point Likert items ranging from 1 (nondiagnostic) to 5 (excellent). The apparent signal-to-noise ratio and apparent contrast-to-noise ratio were evaluated. PI-RADS scores were assessed for both sequences. Statistical analysis was performed by using Wilcoxon signed rank test and paired samples t test. Intrarater and interrater reliability of qualitative image evaluation was assessed using intraclass correlation coefficient (ICC) estimates. Results: A total of 29 male participants were included (mean age, 66 ± 8 years). The acquisition time of the T2CS sequence was respectively 26% (axial plane) and 24% (sagittal plane) shorter compared with the T2conv sequence (eg, axial: 171 vs 232 seconds; P < 0.001). In the axial plane, the T2CS sequence had fewer artifacts (4 [4–4.5] vs 4 [3–4]; P < 0.001), better image-sharpness (4 [4–4.5] vs 3 [3–3.5]; P < 0.001), better capsule delineation (4 [3–4] vs 3 [3–3.5]; P < 0.001), and better overall image quality (4 [4–4] vs 4 [3–4]; P < 0.001) compared with the T2conv sequence. The ratings of lesion conspicuity were similar (4 [4–4] vs 4 [3–4]; P = 0.166). In the sagittal plane, the T2CS sequence outperformed the T2conv sequence in the categories artifacts (4 [4–4] vs 3 [3–4]; P < 0.001), image sharpness (4 [4–5] vs 4 [3–4]; P < 0.001), lesion conspicuity (4 [4–4] vs 4 [3–4]; P = 0.002), and overall image quality (4 [4–4] vs 4 [3–4]; P = 0.002). Capsule delineation was similar between both sequences (3 [3–4] vs 3 [3–3]; P = 0.07). Intraobserver and interobserver reliability for qualitative scoring were good (ICC intra: 0.92; ICC inter: 0.86). Quantitative analysis revealed a higher apparent signal-to-noise ratio (eg, axial: 52.2 ± 9.7 vs 22.8 ± 3.6; P < 0.001) and a higher apparent contrast-to-noise ratio (eg, axial: 44.0 ± 9.6 vs 18.6 ± 3.7; P ≤ 0.001) of the T2CS sequence. PI-RADS scores were the same for both sequences in all participants. Conclusions: CS-accelerated T2-weighted propeller acquisition had a superior image quality compared with conventional T2-weighted propeller sequences while significantly reducing the acquisition time.